Managing an Effective Way to Teach Business Ethics - Walls, John Linn (2015)
Unethical behavior is prominent in the business world and typically leads to negative consequences for people and the environment. Business ethics education acknowledges that ethics teaching has a positive effect on business decisions; however, the problem was the lack of information that is specific to the factors and strategies required to best educate students in business ethics. This lack of information is demonstrated by continued ethical lapses. The purpose of this phenomenological study was to research what is known and unknown on the subject of teaching business ethics through a design intended to understand the lived experiences of ethics instructors. The ethical framework for this study was based on the virtue and justice approaches as a technique for analyzing ethical aspects of a decision, with the goal of improving ethical outcomes. Data collection was completed via interview questions regarding a successful strategy of teaching business ethics. To accomplish this goal, 15 business ethics instructors were interviewed individually to record their lived experiences relating to teaching ethics. Information relating to ethics course design, along with missing components, was the topic of questions. Data analysis using open and axial coding generated 7 major theme clusters that include highlighting character and virtue ethics, increasing concern for stakeholders, and employing the teachings of Socrates and other classic scholars as a basis. The implications for positive social change point to an opportunity for business schools to produce socially conscious leaders who engage in ethical conduct